Investigation of Recrystallization Phenomenon of Single Crystal Superalloys for Gas Turbine Applications - D. Seo; P. Au; X. Husang; D. Nagy (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
The production of single crystal (SX) turbine blades represents the current stateof- the-art in Ni-based superalloy design. With complex casting processes and alloy composition modifications, SX superalloys exhibit superior high temperature mechanical properties to their polycrystalline counterparts. Stresses and plastic deformation can occur in SX nickel-base superalloy engine components at various stages during their manufacture and use. For examples, stresses are created during initial solidification and also during solid state processing such as shot peening, grit blasting, blending, electrodischarge machining and welding. Stresses may also be created during service due to random events such as foreign object impacts. Subsequent exposure of SX to high temperatures during solution heat treatment and brazing repair can result in recrystallization which has been shown to be detrimental to both creep rupture strength and fatigue performance of the components. It is therefore the objective of this paper to understand the recrystallization behavior of two SX superalloys, PWA 1484 and 1483, subjected to pre-stressing and subsequent heat treatments.